Design and Development of M/G/1 Queuing model for Real Time Applications - et. al., N. Paranjothi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The questions relevant to the queuing system’s performance can be addressed by considering the available information of user demand and system capacity. This system can evaluate based on different parameters such as service denial, service duration, response time, etc. Based on analytic tools of Queuing Theory, the desired evaluation of performance is not able to conduct, since the models are of specific kinds for arrival and service processes. The system performance is evaluated based on the simulation. The case of a Spotify back-end server is considered in this work that utilizes in the well-known on-line media-streaming service. A set of models is provided that demonstrates the service capabilities of the band-end server and the user demand. The proposed method is measure the performance of a system based on the simulation of behaviour towards the user input demand.